The validity and reliability of a biofeedback system during segmental stabilisation in patients with low back pain - Pienaar, Andries Willem (Stellenbosch : University of Stellenbosch, 2009)
Thesis (DPhil (Sport Science))—University of Stellenbosch, 2006.